Anxiolytic-Like Profile of Propofol, a General Anesthetic, in the Plus-Maze Test in Mice - Kurt, M.; Bilge, S.S.; Kukula, O.; Çelik, S.; Kesim, Y. (Polish Academy Sciences Institute Pharmacology, 2003)
The present study was performed to investigate the effect of propofol on anxiety using the elevated plus-maze test. Groups of mice received propofol (20, 40, 60 mg/kg) or diazepam (2 mg/kg), caffeine (3 0 mg/kg), L-arginine (100 mg/kg), m-chlorophenylpiperazine (m-CPP, 2.5 mg/kg) and then were placed in an elevated plus-maze that was composed of two opposite closed arms and two opposite open arms. Propofol (20, 40, 60 mg/kg) and diazepam (2 mg/kg) significantly increased the percentage of time spent in the open arms compared to control. Caffeine (30 mg/kg) and m-CPP (2.5 mg/kg) decreased the percentage of time spent in the open arms and these effects were antagonized when propofol (40 mg/kg) was administered before the test. L-arginine (100 mg/kg) has also produced anxiogenic effect and this effect was not prevented by propofol. All drugs used in this study did not significantly change locomotor activity. These results suggest that propofol has anxiolytic effect in plus-maze test.
Keywords: Anxiety; Elevated Plus-Maze Test; Mice; Propofol